O PAPEL DA EDUCAÇÃO EM TRÊS MOMENTOS DA EVOLUÇÃO DO CAPITALISMO ECONÔMICO: consolidação, organização científica e flexibilização - Castro Neto, Vicente Marques de (2008)
In this dissertation we try to analyze the influence of the economical capitalism upon education. We accomplish, in the first chapter, an historical revision of the evolution of capitalism in the economical field, which has as referential point the world bourgeois conception consolidation, form the capitalist commercial stage, until its industrial phase. Soon after, we verify the Rise of the United States of America, like the world economic power and the profound alterations that ocurred inside the North American factories, with the introduction of the rational organizational model in the line of production. Finally, we focus the current issues, mostrly from the postwar, with the introduction of the new paradigm of production initiated in Toyota´s Japonese factories, the capitalist crisis of 1970, the technological revolution with the new elements arrival, the process of worldwide capital and the new ideological conception that sustains the capitalism policy: the Neo-liberalism. In the second chapter, we word the educational issues at the same historical line of the first chapter, highlighting the role of the educational system as one of the support instruments of the bourgeois idea of world, that establishes itself from its consolidation, fundamentally, with the industrial revolution; Afterwards, with the need of most qualified workmanship from the introduction of the scientific method for goods production and, lately, radicalizing with the need of highly qualified workers to handle the instruments produced by the technological revolution of the last decades. We analyze, as well, the Brazilian education from the colonial to the Empire period, in the military government of 1964 and the adaptation of educational politics in FHC s government for the interests of the international organisms and the international economical politics.